PENGARUH GAYA KEPEMIMPINAN SITUASIAONAL DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA PADA JURUSAN MANAJEMEN ANGKATAN 2017 FAKLUTAS EKONOMI DAN BISNIS UNIVERSITAS ISLAM MALANG - Ashar Ashar; Abd Qodir Djaelani; A. Agus Priyono (UNIVERSITAS ISLAM MALANG, 2019)
AbstractIn the purpose of this study was to determine the effect of the lecturer leadership style on the motivation of the 2017 Department of Management Faculty of Economics and Busines University of Islam Malang students.While the sample used in this study was 84 out of a total population of 520 students. The technique in collecting this research data through questionnaires and data analysis methods used are multiple linear regression analysis.The results of this study indicate that the leadership leadership style (G1) of lecturers at maturity level is incapable and unwilling (M1) has a strong influence in increasing student learning motivation, consulting leadership style (G2) lecturers at maturity levels are incapable but willing ( M2) has a strong influence in increasing student learning motivation, participation leadership style (G3) lecturers at maturity level capable but not willing / hesitant (M3) in increasing student learning motivation and delegate leadership style (G4) lecturers at maturity level are able and willing has a strong influence in increasing student learning motivation. So the leadership style (G1M1, G2M2, G3M3 and G4M4) lecturers had a strong influence in increasing student motivation in the 2017 Department of Management, Faculty of Economics and Business, University of Isalam Malang. Keywords: lecturer leadership style, student learning motivation